2019
DOI: 10.1111/opo.12612
|View full text |Cite
|
Sign up to set email alerts
|

Cycloplegia and spectacle prescribing in children: attitudes of UK optometrists

Abstract: Purpose To survey a large number of UK‐based optometrists, in a variety of settings, to determine current attitudes relating to the use of cycloplegia and spectacle prescribing in children aged ≤11 years. Methods One thousand randomly selected members of the College of Optometrists (UK) were invited to complete an electronic questionnaire. The questionnaire was comprised of 42 questions relating to respondent demographics, practitioner use of cycloplegia and attitudes to using cycloplegia to assess childhood r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…With additional concerns about the presence of strabismus, this increases the importance of having an eye examination 7 . Our results are not surprising, given that Doyle et al 24 . reported that 66% of the optometrists who completed their questionnaire did not examine children under the age of 2 years.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…With additional concerns about the presence of strabismus, this increases the importance of having an eye examination 7 . Our results are not surprising, given that Doyle et al 24 . reported that 66% of the optometrists who completed their questionnaire did not examine children under the age of 2 years.…”
Section: Discussionmentioning
confidence: 57%
“…Doyle et al . reported that most optometrists (77%) do not have a concern about using cycloplegia 24 . Qualified optometrists know the appropriate usage, administration practice, and contraindications of cycloplegic drops and have the skills to use an ophthalmoscope and retinoscope 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be for two reasons: One is the case that the PCL is small and the change value is not obvious when relaxing; Second, the circular bers of cycloplegia and relaxation mainly act on the anterior surface of the lens and have little in uence on the posterior surface. The change of human eye diopter is also related to the use of cycloplegia drugs, and the most suitable cycloplegia drugs should be comprehensively selected according to the patient's age, refractive state and other basic conditions [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…One additional reason for a referral might be the need for cycloplegic refraction, which, unlike in other countries (e.g. United Kingdom (Doyle et al, 2019)), cannot be independently performed by Italian optometrists. Although cycloplegia represents the standard procedure for the determination of refractive error in paediatric practice (American Optometric Association, 2017), clinicians can typically measure refraction reliably without cycloplegia from adolescence onward.…”
Section: Figurementioning
confidence: 99%